Nursing students’ knowledge, attitudes, and behaviors toward aging and ageism in Palestine - Bahaaeddin M. Hammad; Basma Salameh; Faeda A. Eqtait; Kassabry Maysa; Imad H. Fashafsheh; Ahmad J. Ayed; Mohamed E.H. Elzeky; Rasmieh Anabtawi; Mohammed F. Hayek (BMC Geriatrics)
Abstract Background Nursing students, as future healthcare professionals, hold a crucial role in delivering high-quality care to older adults. Their ability to provide effective geriatric care depends significantly on comprehensive knowledge and the cultivation of positive attitudes, and behaviors. Recognizing this critical responsibility, this study aimed to assess nursing students’ attitudes, behaviors, and knowledge regarding aging and ageism. Methods A cross sectional study was conducted with a convenience sample from 334 nursing students during Spring 2024. Data were collected using a self-administered questionnaire, including the Facts on Aging Quiz (knowledge assessment), the Relating to Older People Evaluation (ageist behaviors), and Kogan’s Attitudes toward Older People Scale. Results Results revealed significant knowledge gaps, with only a small percentage achieving an acceptable knowledge level. Ageist attitudes were prevalent, though positive attitudes outweighed negative ones. Students generally held somewhat positive views of aging, but negative behaviors persisted, particularly among female students. Work experience with older adults and a family history of caregiving were positively associated with higher knowledge scores. Additionally, satisfaction with nursing education and Confidence in caring for older adults were strongly associated with positive behaviors, attitudes, and knowledge regarding older adults. Correlation analysis showed positive relationships between knowledge, attitudes, and behaviors, with attitudes significantly predicting behaviors in regression analysis. Conclusion Nursing students demonstrated insufficient knowledge about older adults, with positive attitudes and behaviors prevailing despite persistent negative behaviors. Female students exhibited higher negative behaviors, while work experience and caregiving history correlated with better knowledge but did not influence attitudes or behaviors. Satisfaction with nursing education and confidence in geriatric caring were strongly linked to positive outcomes. Enhancing nursing curricula with practical, relevant content and opportunities for meaningful interaction with older adults is essential to improve students’ preparedness and foster quality care.